ADSKILT, FORBUNDET, FORENET: Totemistisk praksis på Rossel Island - Liep, John (Tidsskriftet Antropologi, 1997)
John Liep: Separated, Linked, and United: Totemic Practice on Rossel Island Matrilineal clans on Rossel Island, Papua New Guinea have so-called “linked totems” of bird, plant and fish as well as a fourth totem which is an individual snake, crocodile or dugong. Further investigation disclosed that these emblems and sacred animals are both used to distinguish clans and subclans and to unite linked subclans of different clans. Further, individual geographical features of subclan territories mark out territorial as well as symbolic possessions that are likewise used to “think” separation as well as unification of social groups. A minor point of the discussion is that totems serve as vehicles of metaphor as Levi-Strauss emphasized, but also as metonyms which he underplayed. A second, and major, point is that territorial categories and relations which we tend to regard as “economic” may also be part of a totemic symbolic practice.